Studi Analitik Nilai-Nilai Pendidikan dalam Al-Qur'an Surah Al-'Ankabut Ayat 16-25 dalam Pandangan Ibnu Katsir - Wahyudi, Muhammad; Hamdan Syukri (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
The Qur'an is the word of Allah SWT which was revealed gradually (mutawatir) to the Prophet Muhammad SAW through the angel Gabriel and reading it is worship. In addition, the Qur'an also as